The nature of the tenfold God in William Blake's The book of Urizen : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Herrick, Andrea Margaret (Massey University, 1994)
The purpose of this thesis is to elucidate William Blake's theology by examining the nature of his Tenfold God in The Book of Urizen. As this work was the first in an uncompleted series of poems, only half the components that constitute Blake's God appear in it. I therefore investigate the nature of this Tenfold God by examining the aspects of it that manifest themselves in this poem through the characters of Urizen, Los, Enitharmon, Ore, and the remaining unspecified Eternals. It is the roles of these characters and the interrelationships between them that occupy this study.
Keywords: Blake, William, 1757-1827